Classification of European Hotels - Bondar, Daria; Kolomiiets, Alina (My University, 2015)
It`s a well known fact that hotels play an important role nowadays. Sometimes it is even difficult to decide which to choose while travelling.Hotel companies are classified according to various criteria. The most common are: the level of comfort, functional purpose, location, duration, feeding, prices, the form of ownership.
Keywords: classification; класифікація; hotel; готель; criteria; критерії; national standard; національний стандарт; кафедра іноземних мов професійного спрямування